2021
DOI: 10.1371/journal.pone.0259467
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of single products versus fixed-dose combination medicines for hypertension and hyperlipidemia during 2015–2019 in South Korea

Abstract: Background Fixed-dose combinations can simplify prescribing, and numerous combination products exist for hypertension and dyslipidemia in South Korea. This study’s aim was to compare trends in the consumption of single products versus fixed-dose combinations for hypertension and hyperlipidemia. Methods and findings We analyzed the Korean national health insurance claims database from January 2015 through December 2019. Consumption of medicines was calculated using the defined daily dose per 1,000 inhabitants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…[33][34][35] A national drug utilization study in Korea showed a significant increase in FDC usage, indicating their appeal to prescribers. 36) In this study, we found that FDCs were the preferred choice for prescribing a combination of statin and ezetimibe. Statin/ezetimibe FDCs, with 180,837 prescriptions, were prescribed significantly more often than the corresponding FCs, which had 1,292 prescriptions.…”
Section: Discussionmentioning
confidence: 76%
“…[33][34][35] A national drug utilization study in Korea showed a significant increase in FDC usage, indicating their appeal to prescribers. 36) In this study, we found that FDCs were the preferred choice for prescribing a combination of statin and ezetimibe. Statin/ezetimibe FDCs, with 180,837 prescriptions, were prescribed significantly more often than the corresponding FCs, which had 1,292 prescriptions.…”
Section: Discussionmentioning
confidence: 76%
“…Countries where CCBs were not the most commonly prescribed agents were Korea [ 118 ], Indonesia [ 129 ], Pakistan [ 112 ] and Vietnam [ 107 ]. In Korea, an analysis of the national health insurance claims database reported that ARBs were the most commonly prescribed antihypertensives, both as monotherapy and in combination [ 118 ], with > 50% of patients receiving combination therapy [ 134 ].…”
Section: Resultsmentioning
confidence: 99%
“…Countries where CCBs were not the most commonly prescribed agents were Korea [ 118 ], Indonesia [ 129 ], Pakistan [ 112 ] and Vietnam [ 107 ]. In Korea, an analysis of the national health insurance claims database reported that ARBs were the most commonly prescribed antihypertensives, both as monotherapy and in combination [ 118 ], with > 50% of patients receiving combination therapy [ 134 ]. ACEis were also the most commonly prescribed antihypertensive agents in an analysis of prescribing at a hospital in Vietnam ( n = 388) [ 107 ], whereas in Pakistan, ACEis were the second most common class of antihypertensives after β-blockers, according to a survey of general practitioners ( n = 58) and hospital physicians ( n = 42) in Karachi [ 112 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the widespread availability of fixed-dose combination drugs in the market has contributed to the increasing trend in prescription rates. 18 The upward trajectory of fixed-dose combinations underscores a progressive approach in addressing the complexities of multiple conditions, marking a significant stride in optimizing therapeutic strategies for improved patient outcomes.…”
Section: Discussionmentioning
confidence: 99%